2020
DOI: 10.3390/polym12040968
|View full text |Cite
|
Sign up to set email alerts
|

A Heterocyclic Polyurethane with Enhanced Self-Healing Efficiency and Outstanding Recovery of Mechanical Properties

Abstract: A functional polyurethane based on the heterocyclic group was synthesized and its self-healing and mechanical properties were examined. To synthesize a heterocyclic polyurethane, a polyol and a heterocyclic compound with di-hydroxyl groups at both ends were blended and the blended solution was reacted with a crosslinker containing multiple isocyanate groups. The heterocyclic polyurethane demonstrates better self-healing efficiency than the conventional polyurethane with no heterocyclic groups. Furthermore, unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It has been reported that self-healing materials usually have a trade-off relationship between self-healing ability and mechanical strength [ 19 , 20 , 23 ]. Figure 5 and Figure 6 illustrate the essential benefits of the self-healing PCMs developed in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that self-healing materials usually have a trade-off relationship between self-healing ability and mechanical strength [ 19 , 20 , 23 ]. Figure 5 and Figure 6 illustrate the essential benefits of the self-healing PCMs developed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Intrinsic self-healing materials exploit reversible interactions between the components in the matrix for self-repair. Reversible interactions are classified as chemical (Diels–Alder reactions [ 10 , 11 , 12 ] and disulfide bonds [ 13 , 14 , 15 ]) or physical (host–guest interactions [ 16 , 17 ], hydrogen bonding interactions [ 18 , 19 , 20 ], ionic interactions [ 21 , 22 , 23 ], metal–ligand interactions [ 24 , 25 , 26 ], and π–π interactions [ 27 , 28 , 29 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PU, like many other self-healing materials, faces a trade-off between mechanical strength and self-healing capacity, which can result in compromised restoration of mechanical properties after damage occurs. 17,19 However, a significant challenge lies in understanding the dielectric properties of PU. This study aimed to investigate the dielectric characteristics of PU with different levels of hardness.…”
Section: ■ Introductionmentioning
confidence: 99%
“…PUs are composed of urethane repeating units. The synthesis of PUs involves polymerizing polyisocyanates and macropolyols and the inclusion of chain extenders. The macropolyols, such as polyether diols or polyester diols, are the soft segments. In contrast, the isocyanates (aromatic or aliphatic) and chain extenders (small diols or diamines) are known as the hard segment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some researchers introduced the biological self-healing characteristics and mechanisms into polymer materials and formed functional self-healing materials through bionic design. These materials can recover their original properties spontaneously after damage or under external stimulation, resulting in new intelligent/smart materials with longer lives and more reliable performances, such as shaped memory polymer [ 1 , 2 , 3 ] and self-healing polymer [ 4 , 5 ] intelligent polymer materials.…”
Section: Introductionmentioning
confidence: 99%